1997
DOI: 10.1038/sj.bjp.0701144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of copper on nitric oxide synthase and guanylyl cyclase activity in the rat isolated aorta

Abstract: 1 The potential role of copper (Cu 2+ ) in modulating the activity of nitric oxide synthase (NOS) and guanylyl cyclase (GC) was investigated by use of diethyldithiocarbamic acid (DEDCA), a high a nity Cu 2+ chelator. 2 DEDCA 100 mM inhibited sodium nitroprusside (SNP; 0.005 ± 10 mM)-evoked relaxation of rat isolated aortic rings precontracted with 3 mM phenylephrine (PE). A lower concentration of DEDCA (10 mM) did not signi®cantly attenuate SNP-evoked responses but did inhibit relaxation to the endothelium-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 21 publications
4
24
1
1
Order By: Relevance
“…1A), which was consistent with the previous reports [8,10]. However, in the presence of L-NAME, copper pretreatment still antagonized NA-induced vasoconstriction.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…1A), which was consistent with the previous reports [8,10]. However, in the presence of L-NAME, copper pretreatment still antagonized NA-induced vasoconstriction.…”
Section: Discussionsupporting
confidence: 83%
“…Indeed, many studies reported that NO was generated markedly in sepsis animal models and septic patients [22,23,24]. Based on that copper stimulated NO production [8,9,10], it was reasonable to speculate that copper might be involved in the vascular hyporeactivity in sepsis through enhancing NO action. However, DTC injection (iv) could not reverse the copper-induced hypotension and could not prevent vascular hyporeactivity to norepinephrine in copper-treated rabbits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, an ability of copper ions (Cu 2ϩ ) to relax vessels seems well established. It has been shown that copper enhances the relaxation of precontracted aortic rings evoked by the calcium ionophore A23187 and sodium nitroprusside (30), and it also elevates intracellular cGMP levels and induces relaxation of pulmonary arterial rings (31). More recently, it has been demonstrated that copper induces the activation of eNOS in cultured endothelial cells (32), an event supposed to occur in vivo in hypercupremic states induced by Cu 2ϩ released by ceruloplasmin.…”
Section: Ceruloplasmin (Cp)mentioning
confidence: 99%
“…Такие МИКРОЭЛЕМЕНТЫ В МЕДИЦИНЕ: ОРИГИНАЛЬНЫЕ СТАТЬИ микроэлементы, как селен, хром, цинк, марганец, медь и другие сами являются антиоксидантами ( Zangieva et al, 2013). Медь является кофактором антиоксидантого фермента супероксиддисмутазы: Сu-Zn CОД (Plane et al, 1997;Tsimikas et al, 2012;Azizova et al, 2013;Baskin et al, 2014;Eom et al, 2014). Итак, микроэлементы являются компонентом нейротрофической системы мозга и наравне с це-ребральным энергообменом могут служить марке-рами сохранности мозговой ткани и задолго до клинического проявления сигнализировать об уси-лении патологического процесса в работе ЦНС.…”
Section: Introductionunclassified